Pengembangan Buku Ajar Berbasis Etnomatematika Materi Geometri pada Rumah Budaya Banda Naira - Hayalan, Fitraya; Kepa, Shafriaty; Tuharea, Ammar Amarullah (Lembaga Layanan Pendidikan Tinggi Wilayah XII, 2025)
The purpose of this study was to determine whether eighth-grade mathematics teachers at SMP 82 Central Maluku experience difficulties in delivering mathematical content in their lessons. As a preventive measure, the researcher will develop a textbook on ethnomathematics in geometry to guide teachers in their instructional practice. The object of this study is the Banda Naira Cultural House. This research employs a collaborative approach that combines exploratory and developmental methods. The study consists of two stages: first, the researcher explores mathematical concepts found within the cultural house; second, the researcher develops ethnomathematics-based teaching materials derived from these concepts, resulting in a student textbook. The researchers conducted the study at the Banda Naira Cultural House in Nusantara Village, Banda Naira District, Central Maluku Regency, Maluku Province, Indonesia. Data collection techniques included observation, questionnaires, interviews, and documentation. The researchers used these instruments to collect data on textbook validation results, implementation of teaching materials, teachers’ classroom management skills, student responses to learning activities, student feedback on the textbook, and findings from the pilot study. The data analysis technique used in this study was qualitative, based on observation and interview results.